Austrian height and body proportion references for children aged 4 to under 19 years. (16th April 2013) - Gleiss, Andreas; Lassi, Michael; Blümel, Peter; Borkenstein, Martin; Kapelari, Klaus; Mayer, Michael; Schemper, Michael; Häusler, Gabriele
Abstract: Background : Previous studies have demonstrated differences between national and the WHO reference curves in children older than 5 years. Moreover, reference curves for body proportions (sitting height, subischial leg length and their ratio) based on state-of-the-art statistics are not available. Aim : To develop reference curves for height and body proportions for use in Austria and compare the curves with WHO reference curves. To estimate and statistically investigate extreme percentiles. Subjects and methods : A sample of ∼14 500 children between 4–19 years of age was drawn via schooling institutions, stratified by provinces according to age- and sex-specific population proportions. GAMLSS models were used for a flexible estimation of percentile curves. Results and conclusions : After the age of 5 years national reference curves are more suitable than the WHO reference curves for clinical use in Austria. These height curves are very similar to the German reference curves published recently. Therefore, these reference curves for criteria of body proportions are recommended for use in other populations. Further validation studies are needed to establish whether the recently recommended −2.5 and −3.0 SD for height are a sensitive and specific cut-off in the diagnostic work-up for children with a suspected growth disorder using this new Austrian height chart.